Understanding Cultural Persistence and Change - Paola Giuliano; Nathan Nunn (Institute of Labor Economics (IZA), 2017)
When does culture persist and when does it change? We examine a determinant that has been put forth in the anthropology literature: the variability of the environment from one generation to the next. A prediction, which emerges from a class of existing models from evolutionary anthropology, is that following the customs of the previous generation is relatively more beneficial in stable environments where the culture that has evolved up to the previous generation is more likely to be relevant for the subsequent generation. We test this hypothesis by measuring the variability of average temperature across 20-year generations from 500–1900. Looking across countries, ethnic groups, and the descendants of immigrants, we find that populations with ancestors who lived in environments with more stability from one generation to the next place a greater importance in maintaining tradition today. These populations also exhibit more persistence in their traditions over time.
Keywords: N10; Q54; 330; cultural persistence; cultural change; tradition